The role of Organizational Commitment to Sustainable Performance. A study on Manufactur Company - Dini, Yuli Indah Fajar; Sisilia, Desy; Anggraini, Ratih (Universitas Muhammadiyah Pontianak, 2026)
This study investigates how organizational commitment influences sustainable performance among manufacturing employees in Batam. Data from 359 respondents were analyzed using PLS-SEM. Results show that psychological capital and organizational commitment positively affect sustainable performance. While transformational and transactional leadership enhance organizational commitment, neither significantly impacts sustainable performance directly. Organizational commitment mediates the effects of psychological capital and transformational leadership on sustainable performance, but not that of transactional leadership. These findings offer insights for leadership development aimed at improving sustainable performance in manufacturing.